Effectiveness of Mental Health Literacy in Group Guidance Against Mental Health Stigma - Isma Isma; Ikhlas Rasido; Dhevy Puswiartika; Hasan Hasan (Journal of General Education and Humanities, 2026)
Low mental health literacy contributes to high mental health stigma among students. This study aims to examine the effectiveness of mental health literacy-based group counselling services in reducing mental health stigma among students at MAN 1 Kota Palu. The study uses a quantitative approach with a pretest–posttest control group quasi-experimental design. The sample comprised 21 students, divided into an experimental and a control group. The experimental group received six sessions of mental health literacy-based group counselling services, while the control group did not receive any treatment. The research instruments used were the Mental Health Literacy Questionnaire–Short Version Adult (MHLq-SVa) and the Mental Health Stigma Scale. Data analysis was performed using the Wilcoxon and Mann–Whitney tests. The results showed a significant increase in mental health literacy and a decrease in mental health stigma in the experimental group (p < 0.05), as well as a significant difference between the experimental and control groups (p = 0.000). These findings indicate that mental health literacy-based group counselling is an effective psychosocial intervention in school settings.